Neonatal meningitis according to the microbiological diagnosis: A decade of experience in a tertiary center - Bentlin, Maria Regina [UNESP]; Ferreira, Gabriel Luís [UNESP]; de Souza Rugolo, Ligia Maria Suppo [UNESP]; Silva, Geraldo Henrique Soares [UNESP]; Mondelli, Alessandro Lia [UNESP]; Rugolo Júnior, Antonio [UNESP] (FapUNIFESP (SciELO), 2010)
The aim of this study was to evaluate the incidence of and mortality due to meningitis and compare data according to microbiological diagnosis. This was a ten-year retrospective study conducted at a neonatal intensive care unit (NICU). Newborns with meningitis confirmed by positive CSF culture were included; those with congenital infection or malformations that made lumbar puncture impossible were excluded. The variables investigated were birth weight, gestational and postnatal age, procedures, hematological and CSF parameters, and complications. Parametric and non-parametric tests were used (statistical value p<0.05). The incidence of meningitis was 0.6% and mortality was 27%. Of the 22 cases, 59% involved Gram-negative bacteria; 36% Gram-positive and 5% fungi. The groups did not differ in relation to birth weight, gestational and postnatal age, procedures or hematological and CSF parameters. Sepsis, convulsions and deaths were frequent in both groups, without statistical difference. Gram-negative cases showed abscesses and higher frequency of ventriculitis and hydrocephaly. Meningitis was infrequent, but presented high mortality and frequent complications.
Meningite neonatal de acordo com diagnóstico microbiológico: Uma década de experiência em centro terciário
Keywords: Central nervous system; Meningitis; Newborn; Sepsis